Characteristics and incidence of vaccine adverse events after Bacille Calmette–Guérin vaccination: A national surveillance study in Japan from 2013 to 2017. Issue 33 (5th August 2022) - Okuno, Hideo; Satoh, Hiroshi; Morino, Saeko; Arai, Satoru; Ochiai, Masaki; Fujita, Kentaro; Naito, Seishiro; Kato, Atsushi; Ishii, Koji; Oishi, Kazunori; Suzuki, Motoi; Tanaka-Taya, Keiko
Abstract: Background: Japan amended the recommended age for the Bacille Calmette–Guérin (BCG) vaccination to less than 6 months after 2005, but subsequently amended the recommended age to 5–8 months (latest amendment, <1 year) in April 2013 due to the increasing incidence of BCG-associated osteitis/osteomyelitis since 2005. Methods: We collected data on BCG-associated vaccine adverse events (VAEs) in the population aged <1 year between April 2013 and March 2017. The incidence of BCG-associated VAE was analyzed using census and vaccine coverage data from the government website. We compared the incidence of VAEs in patients vaccinated at less than 6 months with those vaccinated at 6 months or older. Results: Among the 581 BCG-associated VAEs recorded during the study period, 354 (61%) were male, and the average age at vaccination was 5.7 months. The incidence of VAEs per million population aged <1 year at vaccination was highest for suppurative lymphadenitis (63.7), followed by skin lesions (38.4), and BCG-associated osteitis/osteomyelitis (3.1). Disseminated BCG and anaphylaxis were rare (1.1 and 1.6%, respectively). The incidence of VAEs in the population vaccinated at <6 months of age was higher for BCG-associated osteitis/osteomyelitis (3.8) and disseminated BCG (1.3) than in the population vaccinated at ≥6 months. Conclusions: The population vaccinated at <6 months of age was more likely to develop BCG-associated osteitis/osteomyelitis than the population vaccinated at ≥6 months of age, indicating that the change in the recommended vaccination age in 2013 might have contributed to the subsequent decrease in the incidence of BCG-associated osteitis/osteomyelitis.